1977
DOI: 10.1080/00207217708900678
|View full text |Cite
|
Sign up to set email alerts
|

A general unified approach to modelling switching-converter power stages

Abstract: A method for modelling switching-converter power stages is developed, whose starting point is the unified state-space representation of the switched networks and whose end result is either a complete state-space description or its equivalent small-signal low<-f requency linear circuit model. A new canonical circuit model is proposed, whose fixed topology contains all the essential inputr-output and control properties of any dc-todc switching converter, regardless of its detailed configuration, and by which dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
216
0
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,342 publications
(228 citation statements)
references
References 6 publications
0
216
0
4
Order By: Relevance
“…The small signal [5][6][7] modeling of dc-dc switched-mode boost converter transfer function is written in equation (1). (1), it has been observed that a righthalf plane zero presents in the transfer function of boostconverter.…”
Section: A Transfer Function Of Boost Convertermentioning
confidence: 99%
See 1 more Smart Citation
“…The small signal [5][6][7] modeling of dc-dc switched-mode boost converter transfer function is written in equation (1). (1), it has been observed that a righthalf plane zero presents in the transfer function of boostconverter.…”
Section: A Transfer Function Of Boost Convertermentioning
confidence: 99%
“…For this reason Typecontrollers [4] are best suited. The state-space averaging [5][6][7] methods have been used for mathematical modelling of converter. The main objective of this paper is to design Type-III controller for a boost converter and check the converter's closed loop stability in time and frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…These averaging methods can be useful for computing the steady-state and performing stability analysis by setting to zero and linearizing the averaged model, respectively. Averaging theory based on classical Russian averaging techniques is widely used in the analysis of PWM-based power-electronic systems [20]. However, this state-space averaging method may show discrepancies at lower switching frequencies and, therefore, is limited to systems with time discontinuities and large ripple conditions.…”
Section: B Numerical Differentiation Proceduresmentioning
confidence: 99%
“…The SC is modelled using a classical dynamic model composed with a (R-C) series circuit. The average modeling methodology, see [14] or [15], is then used to obtain a non-linear average model of the switching system, given by the following set of equations:…”
Section: System Modellingmentioning
confidence: 99%